2017
DOI: 10.1016/j.jtho.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Lung Adenocarcinoma and Squamous Cell Carcinoma Gene Expression Subtypes Demonstrate Significant Differences in Tumor Immune Landscape

Abstract: Molecular expression subtypes of lung AD and SCC demonstrate key and reproducible differences in immune host response. Evaluation of tumor expression subtypes as potential biomarkers for immunotherapy should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
119
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 33 publications
18
119
2
1
Order By: Relevance
“…We here observed that LUSC seems to be immune-compromised with a signature of massive down-regulation of the complement cascade and other key genes for native immune response. Our results nicely fit within the recent scenario of overall difference in tumor immune landscape in LUAD and LUSC [61].…”
Section: Discussionsupporting
confidence: 90%
“…We here observed that LUSC seems to be immune-compromised with a signature of massive down-regulation of the complement cascade and other key genes for native immune response. Our results nicely fit within the recent scenario of overall difference in tumor immune landscape in LUAD and LUSC [61].…”
Section: Discussionsupporting
confidence: 90%
“…In expression subtypes, earlier findings of more immunological activity in the AD TRU and PI expression subtypes and the SCC secretory expression subtype were confirmed (Faruki et al ., ). In AD, all expression subtypes showed higher estimates of the three T effector cells Th1 cells, Th2 cells, and Tgd cells compared to normal lung.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of expression between subtypes was performed using Kruskal-Wallis ANOVA. Immune signatures were calculated as previously described (30)(31)(32).…”
Section: Bioinformaticsmentioning
confidence: 99%